Auditoría de cumplimiento y su relación con las obligaciones tributarias de la empresa Belitex s.a., cantón Quevedo, año 2014 - Araujo Maldonado, Jeniffer Lisbeth (2016)
This research paper titled "AUDIT COMPLIANCE AND ITS RELATIONSHIP WITH TAX OBLIGATIONS OF THE COMPANY S.A. BELITEX, CANTON QUEVEDO, 2014 YEAR". It is done by the need to audit compliance Tax Company, for the purpose of issuing a proper opinion based on Auditing Standards Generally Accepted Law Internal Taxation and other agreements and regulations, for it was necessary to reconcile financial accounts and stated in the audited year, and determine possible contingent and suggest corrections, internal control was applied by COSO I where it was found that the company has a confidence level of 56,20% considered moderate decline and a risk level of 43 , 80% moderate high, accounting and tax processes, and the degree of compliance is low and dissatisfaction for the audit, because they are not paying claims on time generating expenses for penalties and interest. By tax reconciliation it was confirmed that there is a low level of confidence in the information so that differences between the declared monthly VAT, withholding of Income Tax on the annual income is found and what is recorded in the books. With all these results we proceeded to prepare the report Tax Compliance Based on the models proposed by the Tax Administration for the Independent Audit. Recommending establish control procedures that allow identify compliance by frequent external audits, perform the respective correction of the declaration of income tax as there are differences. All information reflected in this research work is supported by the information provided by the company with the prior approval of its directors, which is being used only for academic purposes.